PENGARUH MODEL PEMBELAJARAN POED (PREDICT-OBSERVE-EXPLAIN-DO) TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN HUKUM DASAR KIMIA KELAS X SMAN 11 JAKARTA - Rahma Nurmalita; Sukro Muhab; Edith Allanas (Jurnal Riset Pendidikan Kimia (JRPK), 2025)
This study was conducted to analyze the effect of POED (Predict-Observe-Explain-Do) learning model on students' critical thinking skills at SMAN 11 Jakarta on the material of basic laws of chemistry. The quantitative research method in this research is quasi experiment with posttest only control group design. Sampling using purposive sampling in class X SMAN 11 Jakarta. Data collection using test instruments in the form of descriptions. Data testing was analyzed using descriptive statistical analysis and inferential statistics (t-test). Based on the results of the study, the data obtained from the posttest value of critical thinking skills of experimental class students is 84,80 while the average value of the control class is 77,89. Meanwhile, the independent sample t-test data obtained sig. (2-tailed) of 0,001 < 0,05 with the effect size of the research data results of 1,454 > 1 in the category of obtaining a very large influence. Based on the analysis of research data, there is a significant difference between the experimental class and the control class. The increase in critical thinking skills with the POED (Predict-Observe-Explain-Doing) learning model is influenced by the learning process systematically and in depth, so that it hones the critical thinking skills of students. It can be concluded in the study that there is an effect of the application of the POED (Predict-Observe-Explain-Doing) learning model on the critical thinking skills of class X students at SMAN 11 Jakarta on the material of the basic laws of chemistry.